Atrocities and confrontational tension - Klusemann, Stefan (Frontiers in Behavioral Neuroscience, 2009)
This paper presents an analysis of video-recordings and other micro-level data of the 1995 Srebrenica massacre in Bosnia-and-Herzegovina. It focuses on the sequential unfolding of micro-interactions and emotional dynamics before, and over the course of the atrocity. The paper argues that massacres have a pattern of situational emergence: local emotional dynamics are crucial to explain where and when atrocities do or do not come off and what form they take on the micro-level. It is shown that (1) micro-interactions constitute situational turning-points, towards or away from atrocities and that (2) local emotional dynamics shape the internal structure of atrocities, i.e., their internal dynamics of killings. The analysis is based on recent advances in the micro-sociology of violence by Collins, Katz, and Grossman, as well as Ekman's research tools for identifying emotional cues in micro-data.